SYSTEMATIC ANALYSIS ON HOW ASANA AND PRANAYAMA YOGA AFFECTS STRESS LEVELS IN MEDICAL STUDENTS - Putri, Nabila Adithya; Prastowo, Nawanto Agung; Suryani, Eva; Amita, Angela Shinta Dewi (Universitas Gadjah Mada, 2023)
Background: Medical students are susceptible to mental illnesses that are brought on by expectations for exceeding academic success. To avoid more serious risks in the future, medical students must manage their stress because it contributes to anxiety, depression, sleep issues, and decreased academic success. Regular yoga practice is one effective and efficient lifestyle modification that can be used to handle stress. This systematic review shows how yoga can help medical students feel less stressed. This study aims to determine the effect between the duration and frequency of Asana and Pranayama Yoga on stress levels in medical students.Methods: Studies till 2022 are used in this systematic review. Articles were accumulated using PubMed, ProQuest, and EBSCOhost. Each search engine has its own designated keywords. Studies were assessed using the NHLBI Study Quality Assessment Tools. Ten studies met the criteria for this study and were all used and analyzed. Results: There were ten studies that met this systematic review criteria and were rated as having good quality by the NHLBI quality assessment tool. All studies showed an association between the frequency of yoga sessions and reduced stress in medical students. Some studies had shorter yoga sessions than others, so the duration of each session did not affect the results as much as the frequency. Conclusion: This study shows that the frequency of yoga sessions has an impact, resulting in lower stress levels in medical students. The impact of yoga duration is minimal when compared to yoga frequency. Yoga should be applied as an intervention to increase the quality of life of medical students.